2016
DOI: 10.1007/s00011-016-0929-y
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled breath markers of alveolar macrophage activity in sarcoidosis

Abstract: Total protein and TNF-α concentrations were elevated in EBC from patients with sarcoidosis and could indicate disease activity. The reduction in EBC Ca(2+) concentrations could represent granulomatous activity in the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…In our study, TNF-α was detectable in the EBC of all subjects, as in previous studies in chronic obstructive pulmonary disease (COPD) (Ko et al, 2009) but unlike in cleaning workers with asthma for which the detection rate was lower (30%) (Viczaya et al, 2013). Values measured in our study were similar to those measured in other healthy population but were lower than those reported in sarcoidosis (3.37 pg.mL -1 ) and in systemic sclerosis patients (13.5 pg.mL -1 ) (Mohan et al, 2016;Edmé et al, 2008). As salivary contamination could occur in EBC sampling, it is worth noting that salivary influence on the cytokine assessment in EBC may be negligible (Ichikawa et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, TNF-α was detectable in the EBC of all subjects, as in previous studies in chronic obstructive pulmonary disease (COPD) (Ko et al, 2009) but unlike in cleaning workers with asthma for which the detection rate was lower (30%) (Viczaya et al, 2013). Values measured in our study were similar to those measured in other healthy population but were lower than those reported in sarcoidosis (3.37 pg.mL -1 ) and in systemic sclerosis patients (13.5 pg.mL -1 ) (Mohan et al, 2016;Edmé et al, 2008). As salivary contamination could occur in EBC sampling, it is worth noting that salivary influence on the cytokine assessment in EBC may be negligible (Ichikawa et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Conductivity is evaluated using B-771 LAQUAtwin ® Horiba, where it was measured by the 2-AC bipolar method. In patients with sarcoidosis, conductivity in exhaled breath condensate was significantly higher than healthy controls [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…A subanalysis of these proteins and inflammatory markers is required to specifically identify the important cytokines and signaling proteins involved in sarcoidosis and are differentially expressed. [100][101][102][103] Original work from our laboratory has demonstrated that EBC TGF-β1, an inflammatory mediator involved in sarcoidosis, and neopterin are elevated in patients with sarcoidosis compared with healthy individuals. 102 Another advantage of evaluating EBC biomarkers is that the technique is totally non-invasive.…”
Section: Exhaled Breath Condensatementioning
confidence: 99%
“…60 100 104-107 In order to further develop the EBC technique in clinical care, much work has been focused on standardisation of EBC collection for use in clinical practice. 100 A summary of key studies which demonstrate the BALF biomarkers that are differentially expressed in patients with sarcoidosis compared with healthy controls is demonstrated in table 2 but more work is required to better characterize EBC findings in sarcoidosis and establish those that are most reliable.…”
Section: Exhaled Breath Condensatementioning
confidence: 99%
See 1 more Smart Citation